PENGARUH PUSH UP DAN HAND PADDLE TERHADAP KECEPATAN RENANG GAYA BEBAS 50 METER PADA KLUB TIRTA TUNGGAL SEMARANG - Shelina Putri Oktaviyani; Bertika Kusuma Prastiwi; Fajar Ari Widiyatmoko (Journal of Physical Activity and Sports (JPAS), 2025)
The background of this research is during the observation at the Semarang Tunggal Tirta club, which is faced with a speed of 50 meters per freestyle swim, which is still slow. The purpose of this study is to find out the effect of push-up and hand paddle on the speed of 50 meters of freestyle swimming. The method employed in this study is a pre-experimental quantitative approach, utilising a two-group pretest and posttest design. The subjects in this study are Semarang Tunggal Tirta club athletes, a total of 15 people, with a sample of 10 people who met the results through the purposive sampling technique. This tool is used to train hand strength, such as push-ups and hand paddles. The push-up results data before and after the test convey a value of 17.13%, and the t-test will give a Sig2-Tail impact of 0.000/p< 0.05. The data of the hand paddle results before and after the test conveyed a value of 14.14%, and the t-test would occur, that would occur Sig2 tail of 0,000/p< 0.05. In this study, push-up and hand paddle exercises carried out at the Semarang single tirta club that most influenced the 50 m freestyle swimming speed were the push-up exercise with an increase of 17.13% although both of them increased the free travel performance of 50 meters, but the push-up training program was more effective than the hand paddle exercise.